THE APPROACH OF TEACHING EAR TRAINING FOR UNIVERSITY STUDENT: IN A CASE OF PRIVATE INTERNATIONAL UNIVERSITY IN THAILAND - Kesjamras, Sit (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The study presents a brief summary of the approach in teaching ear training for university student. The study reveals methodology and steps in teaching ear training for the student who have a different level of musical experience, knowledge, and background. The study also mentions other approaches in which ear training are taught outside the university and why other approaches are not taught in the case of a private international university in Thailand.